2016
DOI: 10.1371/journal.pone.0161732
|View full text |Cite
|
Sign up to set email alerts
|

Change in Auxin and Cytokinin Levels Coincides with Altered Expression of Branching Genes during Axillary Bud Outgrowth in Chrysanthemum

Abstract: In the production and breeding of Chrysanthemum sp., shoot branching is an important quality aspect as the outgrowth of axillary buds determines the final plant shape. Bud outgrowth is mainly controlled by apical dominance and the crosstalk between the plant hormones auxin, cytokinin and strigolactone. In this work the hormonal and genetic regulation of axillary bud outgrowth was studied in two differently branching cut flower Chrysanthemum morifolium (Ramat) genotypes. C17 is a split-type which forms an inflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 90 publications
(121 reference statements)
3
35
0
2
Order By: Relevance
“…This labor-intensive process limits the development of the ornamental chrysanthemum industry to a certain extent [1]. Currently, reports on the shoot branching of chrysanthemum focus mainly on the effects of hormones, including strigolactone [2], auxin [3], and cytokinin [4], as well as other factors such as temperature [5] and transcription factor BRC1 [6]. However, few studies have reported on the effect of sugar on the regulation of the shoot branching of chrysanthemum [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This labor-intensive process limits the development of the ornamental chrysanthemum industry to a certain extent [1]. Currently, reports on the shoot branching of chrysanthemum focus mainly on the effects of hormones, including strigolactone [2], auxin [3], and cytokinin [4], as well as other factors such as temperature [5] and transcription factor BRC1 [6]. However, few studies have reported on the effect of sugar on the regulation of the shoot branching of chrysanthemum [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1934, when Thimann and Skoog demonstrated that apical dominance was associated with auxin [17], this hormone has been regarded as the key signal controlling bud outgrowth and apical dominance [18]. The growth of axillary buds is accompanied by auxin export from the buds and an increase in the expression of the auxin transport gene PINs [4,19]. In recent years, studies have shown that the initial signaling molecule regulating plant apical dominance could be sugar rather than auxin [20,21]; and that auxin acts on subsequent continuous growth stages [22].…”
Section: Introductionmentioning
confidence: 99%
“…Auxin produced in the shoot enters the rootward polar auxin transport (PAT) stream and prevents bud outgrowth in at least two ways: by modulating production of cytokinin and strigolactone, which act in the axillary buds (Dun et al 2012;Teichmann and Muhr 2015;Dierck et al 2016), and by regulating auxin flow out of buds (Sachs 1981;Prusinkiewicz et al 2009;Balla et al 2011). The latter response is less pronounced in pea (Chabikwa et al 2019).…”
Section: Systemic Control Of Axillary Meristem Outgrowthmentioning
confidence: 99%
“…Decapitation causes an elevation of sucrose levels followed by a depletion of the endogenous indole-3-acetic acid (IAA) in the polar auxin transport stream, which influences the auxin flux out of the axillary bud contributing to its sustainable growth 1317 . Flowering transition triggers the activation of the upper most axillary buds in a basipetal sequence having a similar effect to decapitation 13,18 . In an annual plant, the relation between flowering and bud activation is easy to trace as its life cycle ends within one growing season.…”
Section: Introductionmentioning
confidence: 99%